Real‐time measurement of repetitive micro bulk motion vector and motion noise removal in optical coherence tomography angiography. Issue 4 (13th January 2021) - Fan, Jinyu; Dong, Caihua; He, Yi; Xing, Lina; Shi, Guohua
Abstract: In this work, we developed a motion estimation and correction method which real‐time obtained the direction and displacement of repetitive micro bulk motion (such as cardiac and respiratory motion) on an SS‐OCT system without additional tracking hardware, and reduced the motion noise in optical coherence tomography angiography (OCTA). In the approach, the direction of repetitive micro bulk motion was considered fixed, and proportional relationships between the motion components in three directions were determined; Then we performed one‐dimension cross‐correlation to obtain depth displacement which was further used to obtain other two motion components, and greatly reduced the computation; The processing speed on a graphic processing unit was 478 pairs of B‐Scans per second, and the measurement range was larger than the range of the angiogram‐based methods. Lastly, corrupt angiograms were recovered by adaptive scan protocol, and reduced acquisition time in comparison with the previous work. Abstract : In this work, a motion estimation and correction method is presented which real‐time obtained the direction and displacement of repetitive micro bulk motion on an SS‐OCT system without additional tracking hardware, and reduced the motion noise in optical coherence tomography angiography (OCTA). The direction of repetitive micro bulk motion was considered fixed, and proportional relationships between the motion components in three directions were determined. One‐dimension cross‐correlation was performed to obtain depth displacement which was further used to obtain other two motion components, and greatly reduced the computation.